2016
DOI: 10.18494/sam.2016.1248
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Design and Experimental Research for An Iron–Gallium Alloy Force Sensor

Abstract: A magnetostrictive force sensor that can be used to measure alternating load is presented. Iron-gallium alloy (Galfenol) is used as the sensing element. The sensor was developed based on a closed structure. A finite element method was employed to optimally design the size of the excitation coil and the flux path. Simulation results show that the flux density distribution can be clearly improved after optimization. Energy efficiency analysis shows that the energy efficiency of the proposed sensor can be increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…(12) The TL properties for charged particles have also been reported. (15,16) In addition, the use of water as a phantom material is standard for reference dosimetry in radiotherapy, and Al 2 O 3 :Cr TLDs can be used under water. A previous study suggested that 2D Al 2 O 3 :Cr TLDs have high applicability for the quality assurance of robotic radiosurgery.…”
Section: Introductionmentioning
confidence: 99%
“…(12) The TL properties for charged particles have also been reported. (15,16) In addition, the use of water as a phantom material is standard for reference dosimetry in radiotherapy, and Al 2 O 3 :Cr TLDs can be used under water. A previous study suggested that 2D Al 2 O 3 :Cr TLDs have high applicability for the quality assurance of robotic radiosurgery.…”
Section: Introductionmentioning
confidence: 99%